Response surface optimization of lead adsorption onto teff straw-derived activated carbon - Sintayehu Shewatatek; Girma Gonfa; Sintayehu Mekuria Hailegiorgis; Belete Tessema (Results in Surfaces and Interfaces)
Water pollution caused by heavy metals, such as lead (Pb), is a persistent global issue. This study investigates the use of teff straw (Eragrostis tef)-based activated carbon (TSAC) as a sustainable and efficient adsorbent for Pb (II) removal from aqueous solutions. TSAC was prepared through H3PO4 activation and calcination. Fourier transform infrared (FTIR), Brunauer-Emmett-Teller (BET), scanning electron microscopy (SEM), and X-ray diffraction (XRD) techniques were used to characterize the TSAC. The obtained TSAC attained highly porosity with a large surface area of 823.63 m2/g. Response surface methodology with central composite design (CCD) was employed to optimize the TSAC preparation condition, identifying optimal conditions of 2.99 M H3PO4 concentration, 5.674 impregnation ratio, and 453.92 °C activation temperature, leading to a maximum Pb (II) removal efficiency of 93.6%. Adsorption isotherm, kinetic, and thermodynamic studies revealed the mechanism and energetics of the adsorption process. The findings demonstrate the potential of TSAC as a low-cost, eco-friendly, and effective adsorbent for the removal of Pb (II) ions from wastewater, contributing to sustainable water treatment solutions. This study shows that activated carbon from teff straw indigenous to Ethiopia was made by impregnating it with H3PO4 to fill the aforementioned gap and utilized to remove PB ions from water.